Interaction of filamin with f-actin in solution. - Wang, K (1977)
Filamin is a major high-molecular-weight protein in smooth muscle which was recently identified and isolated [Wang, K., Ash, J. F. & Singer, S. J. (1975) Proc. Natl. Acad. Sci. U.S.A. 72, 4483-4486]. In the present studies, we shown that highly purified chicken gizzard filamin and muscle F-actin react in solution to form aggregates containing both proteins. Occasionally, these aggregates coagulate and contract into a dense gel in the absence of MgATP or CaATP. Immunofluorescence and electron microscopic studies suggest that the F-actin filaments are collected into fiber bundles and a crosslinked fiber meshwork by the binding of filamin molecules. These studies suggest that the function of filamin intact cells may be to regulate the ultrastructural state of F-actin filaments in a variety of dynamic cellular processes.